Integration of wet-etched GaN nanowires for vertical power transistors - Yu, Feng; Yao, Shengbo; Römer, Friedhard; Witzigmann, Bernd; Wasisto, Hutomo Suryo; Waag, Andreas (Mikro-Nano-Integration - 6. GMM-Workshops, 2016)
A top-down fabrication approach of GaN vertical transistors through integrating vertically aligned nanowires (NWs) has been reported here. By employing wet chemical etching, NWs with smooth a-plane sidewalls as well as special mushroom-like geometry are realized. The diameter of NWs can be controlled to be as small as 50 nm and their aspect ratio can reach up to 60. A fabricated transistor, integrating 99 NWs, exhibits enhancement-mode (E-mode) operation with a threshold voltage of 1.5 V, a high on and off current ratio of 109, a small subthreshold swing of 67 mV/Dec, and a high drain current (Id) output of Id > 10 mA, indicating that such vertical GaN devices are promising for future candidate in power electronics.
CRIS-Team Scopus Importer:2021-06-11